PENGARUH INTENSITAS PENGGUNAAN GADGET TERHADAP HASIL BELAJAR IPS SISWA KELAS VIII MTs. MUHAMMADIYAH 02 PEKANBARU - Endah Ngesti Utami; Sri Kartikowati; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: One of the technology that is developing rapidly today is gadget. Gadgets can have a positive and negative impact on student social studies learning outcomes. With the gadget, students can use it to add learning resources or sources of knowledge that are not obtained in the teaching and learning process in class. This research aims to determine the effect of the intensity of using gadgets on student social studies learning outcomes. The population in this study were students of class VIII MTs. Muhammadiyah 02 Pekanbaru as many as 181 students. With the Slovin formula obtained a sample of 125 students. The data collected were in the form of questionnaire results and Mid Semester Test scores (UTS) for the Odd Semester 2019/2020. Then the collected data were analyzed using simple linear regression method and described. The results obtained in this study indicate that the intensity of the use of gadgets has no significant effect on learning outcomes. This means that the intensity variable of using gadgets (X) only has a small effect on the learning outcome variable (Y).Key Words : Gadget, Student Learning Outcomes